Fragility assessment for the rainfall-induced embankments on silty soils - Zhou, Haizuo; Ma, Fujian; Yu, Xiaoxuan; Zheng, Gang (Frontiers in Built Environment, 2024)
The fragility curve expresses the probability that an asset exceeds some serviceability state for a given level of environmental perturbation or other loadings. It is an important component in the quantitative risk analysis and resilience evaluation of infrastructure exposed to natural hazards. Incidences of over-settlement of embankments are increasingly reported due to more intense and longer-duration rainfall events. This paper develops fragility curves for the rainfall-induced embankment settlement. For this purpose, an embankment incorporating enhanced seepage and displacement analysis within unsaturated soil conditions is modelled based on a reported case history.A Monte Carlo simulation is used for rainfall infiltration and embankment deformation analysis under various rainfall scenarios. Probability values are obtained to achieve three levels of damage states in terms of road embankment settlement. The parametric analysis produces the exceedance probability curves for various rainfall intensities, saturated permeabilities and embankment slope angles. This work offers an efficient tool for assessing fragility to rainfall-induced excessive settlement of embankments.